THE INFLUENCE OF MECHANICALLY ALLOYED MODIFYING MASTER LIGATURES ON STRUCTURE AND PROPERTIES OF WELDED JOINTS - F. G. Lovshenko; G. F. Lovshenko; A. I. Khabibulin (Литьë и металлургия, 2018)
Actual problem of modern welding production is the creation of electrodes for maximum performance and efficiency of the process whithin the required reliability and durability of the structure. A promising way to improve mechanical properties of the weld metal is the implementation of the mechanism of dispersion hardening. Reactionary mechanical alloying is an effective technology of obtaining nanocrystalline modifying ligatures and modifiers. The use of electrodes with an experimental coating containing a mechanically alloyed, composite ligature to resolve transcrystalline type of structure of the weld metal and reduce the grain size by 2.5–3.0 times (from # 8–9 to #11–12) reduces by 20–30% the threshold of cold brittleness and increase by 15– 25% of the mechanical properties of the weld metal.